Pengaruh Dimensi Kepemimpinan Kepala Sekolah, Sistem Penjamin Mutu Internal, Dan Budaya Sekolah Terhadap Mutu Kompetensi Guru SD Negeri 1 Kota Langsa - Azwarni, Azwarni; Oktavia, Andriyani; Nasir, Muhammad; Hariyadi, Fuad; Pahotan, Deddy; Lubis, Hasrita; Wasesa, Supar; Nasti, Nilawati (Graha Mitra Edukasi, 2024)
This research aims to investigate the influence of school principals' leadership, internal quality assurance systems, and school culture on the quality of teacher competence at SD Negeri 1 Kota Langsa. The population consists of 32 teachers at SD Negeri 1 Kota Langsa, and a total sampling technique was employed, involving the entire population as the sample. Data was collected through non-test methods using questionnaires and library studies as research instruments. Data analysis was conducted using the SPSS software, which included descriptive and regression analyses. The research findings reveal the following: Firstly, the leadership of the school principal has a significant and positive influence on the quality of teacher competence at SD Negeri 1 Kota Langsa. This underscores the vital role of the school principal in shaping the quality of teacher competence. Secondly, the study did not find a significant positive influence from the internal quality assurance system on the quality of teacher competence at the school, indicating that the internal quality assurance system might not yet play a significant role in enhancing teacher competence in this context. Thirdly, no significant positive influence was found from school culture on the quality of teacher competence at SD Negeri 1 Kota Langsa. This suggests that school culture may not be a dominant factor in shaping teacher competence. Lastly, the simultaneous test indicates that together, the leadership of the school principal, the internal quality assurance system, and school culture have a significant influence on teacher competence at this school. The primary conclusion is that the school principal's leadership plays a pivotal role in improving teacher competence, while the internal quality assurance system and school culture have not yet demonstrated a significant impact in this context.